LATERAL PERIODONTAL CYST- A CASE REPORT AND LITERATURE REVIEW - Elitsa Deliverska (Peytchinski Publishing, 2020)
Background: Lateral periodontal cyst (LPC) is a rare example of a developmental odontogenic cyst. LPC may clinically be diagnosed as a radicular cyst, keratocyst, ameloblastoma, odontogenic fibroma, odontogenic myxoma or as other types of odontogenic cysts and tumours. Purpose: The aim is to present an unusual two clinical cases of LPC of the upper and lower jaw. Material and methods: We present two cases with histologically proved LPC. The X-ray revealed radiolucent well-defined, circular in shape homogeneous formation around the root of the affected tooth. Results: The treatment of choice was surgery- enucleation of cyst formation. The complete removal of the cysts was successfully performed. The result of the pathophysiological examination of both cases showed LPC. Since after the operation regular follow up was perform and till now there was not any signs of recurrence. Conclusion: LPC is a rare odontogenic cyst of developmental origin, which should be timely diagnosed and surgically removed.